PORTABLE ARDUINO-BASED INTEGRATED WATER QUALITY ANALYZER WITH REAL-TIME DATA TRANSMITTER - Alave, Estelle Nicole L; Lim, Harvey Andrew G; Ronquillo, Jericho L; Tugade, Marjun M (MATTER: International Journal of Science and Technology, 2020)
In our society, there is an accelerated rate of morbidity and mortality worldwide stemming from various water-related diseases. Thus, safety is the most critical factor in decision making for safe-drinking water. Moreover, prompt acquisition of on-the-spot information regarding water quality is still a challenge due to the unavailability of portable devices that can give vital information which hinders the resolution of water-related problems. Another challenge is the transport time of data from one location to another especially from distant or isolated places and the limitation of the locals to interpret the information. In this study, all the problems are solved by the development of a user-friendly portable Arduino-based integrated water quality analyzer which measures the temperature, pH, turbidity, and the total dissolved solids (TDS) of the water which are the core parameters in determining the water quality in just one sitting. Furthermore, the device has a Global System for Mobile Communication (GSM) module which sends real-time data to identified professionals and institutions. To ensure the accuracy of the device, the sensors were subjected to various tests, verifications, and comparisons with standard laboratory equipment. The results show that both the device and the lab equipment had no significant differences, with the data values acquired from the device all falling within ± 5%. The t-test was also done. The p-values for all four parameters are greater than the α value (0.05) which means that the device is indeed accurate with the prototype and laboratory values having no significant difference. The device has great potential in helping people ranging from the locals up to the professionals and institutions by reducing the time of data transport and simplifying the analysis regarding water quality which is crucial in the decision making and action-taking processes of water treatment. The device is expected to be tested in the field as soon as recommendations are well integrated.